2014
DOI: 10.1109/tgrs.2013.2286821
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Optimization of the Extended Kalman Filter’s Parameters Through the Use of the Bias Variance Equilibrium Point Criterion

Abstract: The extraction of information on land cover classes using unsupervised methods has always been of relevance to the remote sensing community. In this paper a novel criterion is proposed which extract the inherent information in an unsupervised fashion from a time series. The criterion is used to fit a parametric model to a time series and derive the corresponding covariance matrices of the parameters for the model and estimate the additive noise on the time series. The proposed criterion uses both spatial and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It either has the ability to assist in improving the true positive rate [17] or it can lower the false positive rate [25]. Our experiments found that the false positive rate was further reduced as shown in Table II when a SVM was used on the 14-dimensional pendulum.…”
Section: B Experimental Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…It either has the ability to assist in improving the true positive rate [17] or it can lower the false positive rate [25]. Our experiments found that the false positive rate was further reduced as shown in Table II when a SVM was used on the 14-dimensional pendulum.…”
Section: B Experimental Resultsmentioning
confidence: 79%
“…As confirmed by (25), the total energy of the pendulum system in the absence of a driving force is constant and equal to the potential energy at the maximum amplitude, namely E = mgL(1 − cos θ) if the potential energy is referenced to the static equilibrium position θ = 0. As shown in Figure 7(a), if the pendulum's amplitude is close to 180…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Secondly, with sufficient characterisation of surface waters at various scales, it could become feasible to deploy more supervised approaches for which example deployments are evidenced in the terrestrial realm. Possible methodologies could include the use of artificial neural networks [83][84][85] and decision tree classifiers [26] on hypertemporal datasets, or more likely, hypertemporal dataset derivatives. Furthermore, categorisation of the ocean's surface into regions exhibiting different temporal profiles could provide opportunities for these profiles to be examined and explored.…”
Section: Classification (Cls)-founded Approachesmentioning
confidence: 99%